Effect of Adding Calcium Dolomite (CaMg(CO3)) and Tohor (CaO) in Cultivation Media to Increase Moulting of Litopenaeus vannamei - Wahyuni, Septia Tri; Lestari, Dewi Putri; Diniariwisan, Damai (Aquaculture Department, University of Mataram, 2024)
Vaname shrimp (Litopenaeus vannamei) is a fishery commodity that is the largest contributor to exports compared to other commodities. The success of shrimp survival and growth cannot be separated from the molting process, which requires calcium. The calcium that absorbed from the cultivation media can play a greater role in the process of exoskeleton formation. Dolomite lime (CaMg(CO3)) and tohor (CaO) can be sources of calcium that can be added to cultivation media. The research method used in this study was a completely randomized design (CRD) consisting of 5 different treatments (A: without additional lime, B: 0.8 gr dolomite, C: 0.8 gr tohor, D: 0.3 gr dolomite + 0.5 gr of tohor, E: 0.5 gr of dolomite + 0.3 gr of tohor) with 3 repetitions. The results showed that the addition of lime at different doses provided a molting frequency ranging from 2.07 – 3.23 times during the 60 days rearing period, where treatment E was the optimum treatment. The absolute weight growth obtained ranged from 2.52 gr – 5.03 gr, with an absolute length of 5.25 cm – 9.11 cm. The highest survival rate during maintenance in treatment E reached 72%. The water quality conditions measured during the activity were alkalinity 135 – 146 ppm, Ca hardness 132.74 – 172.39 ppm, temperature 29.9 – 30.3°C, DO 6.3 – 6.5 mg/l, pH 7 .9 – 8.3 and salinity 32 -34 ppt.